PENERAPAN DIGITAL MARKETING DAN PEMBUATAN NIB SEBAGAI STRATEGI PEMASARAN UMKM - Kader, Mukhtar Abdul; Toto, Toto; Puspita, Endah; Cahyani, Ika; Pauji, Irfan Hilmi (Jurnal Abdi Insani, 2025)
Kertayasa Village is one of the Self-Help Villages which is located quite far from Ciamis Regency and Internet Access is Difficult, with Independent Campus activities in the Independent Learning Campus Independent Program where one of the programs is Thematic Real Work Lectures which are held for one semester. Kertayasa Village was chosen because the village ranking obtained needed to be upgraded to become an independent village, its location is quite far from Ciamis City so that internet access is very difficult, it is hoped that in the future Kertayasa Village will be able to increase its level to become a self-supporting village: its people will be able to use the internet to increase their sales. . This KKNT activity focuses on increasing the capabilities of MSMEs by using various online media. The method used is providing direct assistance with residents, especially teenagers who already have good digital marketing literacy competencies, to small businesses, starting from processing permits, product packaging, creating marketplaces and marketing methods using digital marketing concepts. Micro, small and medium enterprises in Kertayasa village. Several micro businesses already have Business Identification Numbers (NIB). as an identity and increase consumer trust, creating social media, including Instagram Business, Fan Pages, Professional Facebook, YouTube ads. For Micro Businesses that have many types of products aimed at markets such as Shopee and Tokopedia. Next, collaborate with the community, especially youth youth organizations, in disseminating product information through digital marketing concepts. Collaboration between the Faculty of Economics and Kertayasa Village through the creation of a Micro Business NIB, Digital Marketing Assistance is able to increase market size and citizen competency.